2021
DOI: 10.32890/mjli2021.18.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Rubric for Research Report Writing: A Tool for Supervision

Abstract: Purpose – Assessment rubric often lacks rigor and is underutilized. This article reports the effectiveness of the use of several assessment rubrics for a research writing course. Specifically, we examined students’ perceived changes and observed changes in their Chapter 1 thesis writing as assessed by supervisors using an existing departmental rubric and a new task-specific rubric. Methodology – Using action research methodology, two of the authors played active roles as the course supervisors, i.e., the pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…One example of the use of analytic rubrics in Malaysian universities is in the evaluation of student writing. In a study conducted by Bukhari et al (2021), the effectiveness of various assessment rubrics was explored within the context of a research writing course at a Malaysian university. The research findings indicated significant enhancements in the quality of students' writing across three successive drafts.…”
Section: Use Of Holistic and Analysis Rubric In Malaysia's Universitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of the use of analytic rubrics in Malaysian universities is in the evaluation of student writing. In a study conducted by Bukhari et al (2021), the effectiveness of various assessment rubrics was explored within the context of a research writing course at a Malaysian university. The research findings indicated significant enhancements in the quality of students' writing across three successive drafts.…”
Section: Use Of Holistic and Analysis Rubric In Malaysia's Universitiesmentioning
confidence: 99%
“…Notably, the revised rubric contributed to additional and more specific improvements, especially in areas such as literature searches, problem statement formulation, research question development, and operational definitions of variables. Furthermore, there was a broader improvement in writing clarity, with students incorporating examples and offering relevant explanations tailored to their research topics [32]. In another study by Darmi et al (2022), a rubric was proposed for the assessment of innovation teaching practicum.…”
Section: Use Of Holistic and Analysis Rubric In Malaysia's Universitiesmentioning
confidence: 99%
“…In content-driven programs where subject specialists teach their subject matter, students’ compositions are predominantly evaluated on their content. Rubrics employed in these courses commonly entail multiple specific content-related criteria, without dividing linguistic features into minute elements as frequently seen in L2 writing assessment and language-driven CLIL (e.g., Bean & Melzer, 2021; Bukhari et al, 2021; Gao et al, 2019; Garza et al, 2021; Walvoord & Anderson, 2010). For example, the following nine criteria exist in a rubric used at two U.S. universities to assess first-year students’ compositions, including engagement with external sources, originality of the contention, clarity of the contention, effectiveness of supporting evidence, presentation of the writer’s own idea, organization, source use, language style, use of standard written English, and formatting (Walvoord & Anderson, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…4. Writing assessment rubric: Bukhari et al (2021) define a rubric as a measurement tool for comparing and measuring a performance, behaviour, or product. It serves as scoring guide to evaluate the quality of students' work on a given task.…”
Section: Data Collectionmentioning
confidence: 99%